REPRESENTASI DEMONSTRASI 25 AGUSTUS 2025 DALAM FOTO JURNALISTIK PADA MEDIA KOMPAS.ID: ANALISIS SEMIOTIKA ROLAND BARTHES - Andita Ari Putri; Muhammad Bayu Widagdo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The August 25, 2025 demonstration in front of the DPR/MPR RI building attracted widespread public attention and extensive media coverage, including by Kompas.id. Through photojournalism, media not only documents events but also constructs particular representations and meanings. This study aims to analyze the denotative, connotative, and mythological meanings embedded in the photojournalistic coverage of the demonstration published by Kompas.id. Employing a descriptive qualitative approach within a critical paradigm, this research applies Roland Barthes' semiotic analysis to 13 purposively selected photographs. The analysis was conducted through three levels of signification: denotation, connotation, and myth. The findings show that, at the denotative level, the photographs depict various dynamics of the demonstration involving demonstrators, security forces, and crowd-control equipment around the DPR/MPR RI complex. At the connotative level, demonstrators are represented as courageous actors advocating for public interests, while security forces are portrayed as symbols of state authority and control. At the mythological level, four dominant myths emerge: demonstrations as a struggle for justice, the state represented through its coercive security apparatus, nationalism aligned with the people's side, and demonstrations as a contestation arena between citizens and power. This study concludes that Kompas.id's photojournalism functions not only as visual documentation but also as a medium for constructing social and ideological meanings related to the relationship between citizens, the state, and democracy.